If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 = 2(22 + -1x) Reorder the terms: 9 + 3x = 2(22 + -1x) 9 + 3x = (22 * 2 + -1x * 2) 9 + 3x = (44 + -2x) Solving 9 + 3x = 44 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9 + 3x + 2x = 44 + -2x + 2x Combine like terms: 3x + 2x = 5x 9 + 5x = 44 + -2x + 2x Combine like terms: -2x + 2x = 0 9 + 5x = 44 + 0 9 + 5x = 44 Add '-9' to each side of the equation. 9 + -9 + 5x = 44 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 44 + -9 5x = 44 + -9 Combine like terms: 44 + -9 = 35 5x = 35 Divide each side by '5'. x = 7 Simplifying x = 7
| -u+3=2u+6 | | -11/9+1/2x-11/3x=3/2x-12/3-1 | | 15y-18y+1y=-2+40-2 | | 4(x-3)=x+15 | | 21/7+(-7/4)-32/5 | | 182/n=13 | | (y^2-5y+3)(2y^2+7y-4)= | | 6(1+3m)=-9(-2m+5)-4 | | 11n=143 | | (-2/3)+8=(4/3)+6 | | -313/18=-3/2+2/3x | | (r^2)-7r-18=0 | | (-2/3x1)+8=(4/3x1)+6 | | 84/12=n | | 317/18=-1/2-5/3n | | -16=x+6 | | -7y-33=4y | | -53/12-8/12 | | 0.35/4.9x7=X | | 3(x+6)=x+2 | | -52/12-8/12 | | 4/7y+2/-8=-7 | | -4=3y-1+14 | | x^2+2x+(-3)=0 | | (2x-4)(2x+5)= | | 9.6=x/6 | | -5-(5y-1)=2(7y-16)-y | | 5z+32=4(2z+5) | | y/4-3=7 | | -8v-1=4v-1 | | w=1/4(x+y-z) | | -18-2x=36 |